Mobile learning and health education: how students of biomedical laboratory sciences use their mobile devices? - Cardoso, Teresa Margarida Loureiro (2021)
Mobile Learning (M-learning) is an emerging area of distance education that takes advantage of the ubiquitous power of mobile devices, enabling the teaching and learning process by increasing access to information and supporting different types of learning. This article is part of a larger study, exploratory and descriptive, in which the use of mobile devices as a mediation tool in the teaching and learning process in a Portuguese higher school of health was analyzed. The instrument of data collection was a survey, which, in this case, 634 students responded to, with the aim of describing their use of mobile devices in learning contexts. From the data analysis, we perceive that the students mostly acquired their first mobile device at the age of 10 years old. Of these 98% use the Smartphone, mobile phone and tablet every day, and these mobile devices are of the following brands: Samsung (33%), Apple (15%), and Nokia (10%). The Android operating system prevails (70%) over iOS (15%). The features of the mobile devices most used by the students were SMS, alarm clock, and Internet access, with percentages of use greater than or equal to 90%. The importance attributed to the Apps for study and learning is indifferent or rejected for 72% of students. We can conclude, on account of our results, that the participants have, according to our perspective, the two conditions necessary to engage in mobile learning, namely: (i) positive perceptions about mobile devices, essentially in their ability to provide pedagogical advantages; (ii) owning a mobile device, meaning it is possible to implement a Bring your OWN device (BYOD) strategy